70.1k views
1 vote
Expand and Simplify:

(x + 1) (x + 4) (x + 3)
Please help! Due in on Friday and I have 9 other questions as well as this one!
I wasn't in on the day we did this in lesson at school, so someone give me a right answer... please?
-Will give 10 points to the winner Xx

2 Answers

2 votes

Multiple (x+1) (x+4) (x+3)

(x+1) (x+4) FOIL

x² + 5x + 4

(x² + 5x + 4 ) (x + 3) multiple it by x and then 3

x(x² + 5x + 4 ) = x³ + 5x² + 4x

3(x² + 5x + 4 ) = 3x² + 15x + 12

now add them x³ + 8x² + 15x + 12


User Pete Brumm
by
5.6k points
6 votes

Answer:


x^3+8x^2+19x+12

Explanation:


(x+1)(x+4)(x+3)=(x+1)(x^2+3x+4x+12)=(x+1)(x^2+7x+12)=\\ =x^3+7x^2+12x+1x^2+7x+12=x^3+8x^2+19x+12

User Tetsuo
by
7.0k points